ANALYSIS OF SOME RESEARCH ON THE DEVELOPMENT OF COGNITIVE ACTIVITY OF CHILDREN WITH SPECIAL EDUCATION NEEDS - Pulatova Paridakhon Mukhitdinovna; Sardorkhon Yuldashev (The Bioscan, 2025)
The goal defines the expected outcome and outlines the directions for the activities of students with intellectual disabilities and oligophrenopedagogues. Along with the approaches to teaching, the organizational and content structure of the model reflects the content of special corrective education and the results of learning and cognitive activities.